Application of the Five-Minute Rating Method in Measuring Labor Productivity at a Jakarta Office Tower Project - Dian Perwita Sari; Michael Adams Siregar (Borneo Engineering: Jurnal Teknik Sipil, 2026)
Labor productivity is a critical factor in construction projects, directly influencing the successful achievement of time and cost targets. This study aims to analyze the comparison of labor productivity levels between regular hours and overtime using the Five-Minute Rating method. The research was conducted at an Office Tower Construction Project, employing a descriptive quantitative approach. Data was collected through three days of observation of worker activities, which were classified into effective work, ineffective work, and essential contributory work, using a five-minute observation interval. The results indicate a significant difference in productivity between regular and overtime hours. During regular hours, the average Labor Utilization Rate (LUR) reached 60.8%, with the peak pattern occurring in the morning (LUR 60.8%-71.5%) and a decline in the afternoon and evening. In contrast, during overtime hours, the average LUR was lower at 53.6%, showing a progressively more noticeable declining trend throughout the night shift. The average productivity decrease during overtime was 7.2%, with the highest decline recorded on the third day at 9.6%. Dominant factors contributing to the productivity decline during overtime include cumulative fatigue following the regular shift, suboptimal lighting conditions, and an increased proportion of non-productive contributory activities, which reached 30-40% of total activities.